RELEVANCE OF ABNORMAL UTERINE BLEEDING - Temirova Dilnoza Olimzhonovna; Жумаева Дилноза Рустамовна (TADQIQOTLAR, 2025)
GENERAL INFORMATION Abnormal uterine bleeding (AUB) is bleeding that is excessive in duration (more than 8 days), volume of blood loss (more than 80 ml)  and/or  frequency  (interval  less  than  24  days).  Heavy  menstrual  bleeding  is excessive  menstrual  blood  loss,  having  a  negative  impact  on  the  physical,  social, emotional and/or material well-being of a woman. The obsolete terms "menorrhagia", "metrorrhagia",  "hypermenorrhea",  "hypomenorrhea",  "menometrorrhagia", "dysfunctional  uterine  bleeding"  are  currently  replaced  by  AUB,  heavy  menstrual bleeding and intermenstrual bleeding. The concept of "AMB" includes the terms: • heavy menstrual bleeding, which means a heavier or longer period of menstruation, • irregular  and  prolonged  menstrual  bleeding.  However,  anemia  is  not  a  mandatory criterion for heavy uterine bleeding. It should be noted that AUB includes bleeding from the body and cervix of the uterus, but not from the vagina and vulva. Abnormal uterine bleeding (AUB) not associated with pregnancy has remained one of the leading reasons for visiting a gynecologist for many years; the incidence of AUB is about 30% among patients of reproductive age and can reach 70% in the perimenopausal period. Repeated AUB lead to the development of iron deficiency anemia, significantly reduce the quality of life, and are also associated with additional costs for hygiene products.